2022
DOI: 10.1111/1541-4337.12930
|View full text |Cite
|
Sign up to set email alerts
|

An overview of structure engineering to tailor the functionality of monoglyceride oleogels

Abstract: Monoglyceride (MG)‐based oleogelation is an effective strategy to create soft matter structures with the functionality of fats, but with a nutritional profile similar to edible oils. MG oleogels are mainly studied to replace or reduce trans and saturated fats as well as to develop novel products with improved physical and organoleptic properties. The process consists of direct dispersion of MGs into the oil at temperatures above the melting point. This is followed by a cooling period in which the gelator netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 119 publications
(326 reference statements)
1
9
0
Order By: Relevance
“…Due to the addition of proteins, hardness was improved, while the presence of GMS affected thermal behavior and melting properties. The overall increased thermal stability accompanied by higher structural order compared to beef fat was largely due to the presence of GMS in FS, as previously reported in literature 25 , 26 . The higher melting temperature and melting enthalpy of FS compared to beef fat were supportive in preserving the tender texture of CM prototypes while cooking at 250 °C for 6 min.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Due to the addition of proteins, hardness was improved, while the presence of GMS affected thermal behavior and melting properties. The overall increased thermal stability accompanied by higher structural order compared to beef fat was largely due to the presence of GMS in FS, as previously reported in literature 25 , 26 . The higher melting temperature and melting enthalpy of FS compared to beef fat were supportive in preserving the tender texture of CM prototypes while cooking at 250 °C for 6 min.…”
Section: Discussionsupporting
confidence: 83%
“…This is particularly obvious in the burger-like CM where the FS ratio was higher (30% w/w) compared to layered CM (10% w/w), and where hardness increased after cooking. In general, in the case of cooked products, the FS must be able to replicate functionalities related to water and fat binding, thus providing juiciness and preventing water and fat loss during cooking 24 , 25 . Hence, strong intermolecular interactions between the proteins in the oleogel-based FS and proteins in the microtissues considerably enhance the CM integrity 12 , 14 , 24 , 26 , 27 , which in turn leads to lower cooking loss, as observed in both CM prototypes.…”
Section: Discussionmentioning
confidence: 99%
“…The properties of MG oleogels, such as hardness, stability, elasticity, etc., render them suitable for many different food applications [ 14 , 15 , 16 ]. As pointed out in the literature, the structure and the physical properties of the MG oleogels are affected by the type and the concentration of the MGs, the oil type, and the processing conditions, namely temperature, stirring speed, cooling rate, storage temperature and time, etc., as well as the presence of other gelators [ 13 ]. Some studies have recently reported the interaction of MGs with other structuring agents, such as phytosterols [ 17 , 18 , 19 ], ethyl cellulose [ 20 , 21 ], and waxes [ 22 , 23 , 24 ], etc., so that oleogels can be more stable and with more suitable properties, depending on the intended food use.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported that this crystallization type is related to the presence of the β-crystals of MG oleogels [ 48 , 49 ]. The size and the type of crystals can be influenced by a variety of factors, including the concentration of the gelling agent, the type of edible oil used in gel formation, the cooling rate, and the combination with other ingredients [ 19 , 50 ]. However, it is important to note that the addition of SW in combination with MGs as structurants resulted in changes in the crystals’ morphology ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%